2015
DOI: 10.7566/jpsj.84.114707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spin–Orbit Coupling on Kondo Phenomena in f7-Electron Systems

Abstract: In order to promote our basic understanding on the Kondo behavior recently observed in europium compounds, we analyze an impurity Anderson model with seven f electrons at an impurity site by employing a numerical renormalization group method. The local part of the model consists of Coulomb interactions among f electrons, spin-orbit coupling λ, and crystalline electric field (CEF) potentials, while we consider the hybridization V between local f electrons and single-band conduction electrons with au symmetry. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Recently, the existence of a HF state in Eu-based compounds has attracted renewed interest. [23][24][25][26][27][28] This behavior has been clearly evidenced, in particular for the MV compound EuNi 2 P 2 (v = 2.45-2.55), from thermodynamic and transport, 25 as well as spectroscopic measurements.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, the existence of a HF state in Eu-based compounds has attracted renewed interest. [23][24][25][26][27][28] This behavior has been clearly evidenced, in particular for the MV compound EuNi 2 P 2 (v = 2.45-2.55), from thermodynamic and transport, 25 as well as spectroscopic measurements.…”
mentioning
confidence: 91%
“…In a recent paper, 28 Hotta has proposed an interesting theoretical basis to explain how the 4f 7 state of Eu 2+ can give rise to a Kondo phenomenology (including quantum criticality controlled by an external parameter) very similar to that found in nearly trivalent (4f 1 ) Ce compounds. The key argument is that, for realistic values of the spin-orbit coupling, a correct description of atomic 4f states cannot be achieved in terms of the standard Russel-Saunders scheme.…”
Section: Iv2 Dynamic Magnetic Responsementioning
confidence: 99%
“…Recently, the existence of a HF state in Eu-based compounds has attracted renewed interest. [23][24][25][26][27][28] This behavior has been clearly evidenced, in particular for the MV compound EuNi 2 P 2 (v = 2.45-2.55), from thermodynamic and transport, 25 as well as spectroscopic measurements. 24,27 Hossain et al 23 have also reported the observation of Kondo effect with a HF behavior in the EuCu 2 (Si x Ge 1−x ) 2 series.…”
Section: Introductionmentioning
confidence: 76%
“…The valence state of the Eu ion can be tuned easily by external parameters, such as temperature and pressure, because the energy difference between the two valence states is relatively small. 23) In this context, it will be useful to examine the relationship between the valence state and free space of the Eu ion in various Eu-based compounds, since the effective radii of Eu ions are different between the two valence states. EuBe 13 is a valuable material for studying not only the phonon property in MBe 13 systems but also characteristics of the Eu 3+ state.…”
Section: Introductionmentioning
confidence: 99%